Language through translation exploring Alice in Chao Yuen-Ren's Chinese 'Wonderland' - Zhang, Daozhen (Cambridge Scholars Publishing, 2020)
Characterization is a vital issue in creative and imaginative writing for children. Within a communicative framework of systemic functional linguistics, this book reveals how the fantasy characterization is construed in the SL text, and how it is constructed and distorted in the Chinese translation, based on a description and interpretation of the translation shifts, before an explanation is given of the semiotic relationship between those shifts and the characterization. As a work of descriptive translation studies, this book provides approaches to transitivity construal of the characterization.